Development in Language Theory 15th International Conference, DLT 2011, Milan, Italy, July 19-22, 2011. Proceedings - Mauri, Giancarlo; Leporati, Alberto (Theoretical Computer Science and General Issues, 2011)
This book constitutes the refereed proceedings of the 15th International Conference on Developments in Language Theory, DLT 2011, held in Milano, Italy, in July 2011. The 34 regular papers presented were carefully reviewed and selected from numerous submissions. The volume also contains the papers or abstracts of 5 invited speakers, as well as a 2-page abstract for each of the 7 poster papers. The topics covered include grammars, acceptors and transducers for words, trees and graphs; algebraic theories of automata; codes; symbolic dynamics; algorithmic, combinatorial and algebraic properties of words and languages; decidability questions; applications of language theory, including: natural computing, image manipulation and compression, text algorithms, cryptography, concurrency, complexity theory and logic; cellular automata and multidimensional patterns; language theory aspects of quantum computing and bio-computing.